1993
DOI: 10.1207/s15328023top2004_6
|View full text |Cite
|
Sign up to set email alerts
|

An Inexpensive Habituation and Sensitization Learning Laboratory Exercise Using Planarians

Abstract: We dasnik an inexpensiw 1abnmtor)r exerci.ie thar lcres pla. mrians to demonstrate habitunrion and scnsitizaticm. Students drop waterfrom an eyedropper onto a plonarian's anteriw re@ and observe its contraction respaues. Initially. studenti practice the pmcedure until atmining high interobserver reliahilitv in scming the degree of contraction. Subsequently, rhey measure the decline in responciviry that occurs over repeated stimulus presentation~. Fcrllowing Imbin.mtion, the planarion is d r a m in and otir of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This behavior is easy to observe and subject to habituation (Abramson, 1994). In addition, the crabs are large and more physically robust than planaria (Owren & Scheuneman, 1993), which I have found not to survive repeated stimulation by students.…”
Section: Wagner Collegementioning
confidence: 93%
“…This behavior is easy to observe and subject to habituation (Abramson, 1994). In addition, the crabs are large and more physically robust than planaria (Owren & Scheuneman, 1993), which I have found not to survive repeated stimulation by students.…”
Section: Wagner Collegementioning
confidence: 93%
“…Despite the popularity of a habituation preparation in planarians (e.g., Owren & Scheuneman, 1993), near to no attention has been paid to its temporal course. The only study that addressed the effect of repeated presentations of an eliciting stimulus over several days and tested the animals reactivity to the stimulus after an interval of at least 24 hr is that reported by Westerman more than 50 years ago (Westerman, 1963).…”
Section: Methodsmentioning
confidence: 99%
“…Other studies showed that animals’ natural responses to vibration (Dilk, 1937) and changes in luminance (Miller & Mahaffy, 1930) readily habituated. The habituation of the longitudinal contraction in response to a drop of water on the body of the animal has been widely used to demonstrate short-term habituation in the planaria; this observation has become a popular high-school lab demonstration (see, e.g., Owren & Scheuneman, 1993).…”
mentioning
confidence: 99%
“…Habituation seems to function as a concept that describes and directs attention to processes of normalization, accustomation, and the resulting smoothing over of differences. In existing conceptualizations of shared human-animal lives (excluding conventional pets or companion animals), habituation is used to explain a process through which one species becomes accustomed to another's presence, usually a nonhuman animal to a human animal (Candea, 2010;Clay, Bloomsmith, Marr, & Maple, 2009), but it also extends to explaining general processes of accustomation of species such as hamsters (Johnston, 1993) or even flatworms (Owren & Scheuneman, 1993).…”
Section: Origins: #Pigeonsmentioning
confidence: 99%